Experimental and Analytical Evaluation of Transmission Properties of Millimeter Wave Range Metal Grating - V. V. Komarov; A. A. Nevsky (Известия высших учебных заведений России: Радиоэлектроника, 2017)
Metal gratings (MGs) with rectangular lamels based on the technology of jet etching of thin metal plates are widely used in different polarization devices of microwave and terahertz engineering. Numerical methods of mathematical modeling or direct measurements are employed for their analysis. Sometimes in case of H-polarization, analytical approaches for evaluation of transmission characteristics of such gratings can be taken. However, the accuracy of the most of proposed similar models depends essentially upon sizes and frequency ranges. The present article provides both theoretical and experimental research of transmission characteristics of MG with fixed size illuminated by plane electromagnetic wave with H-polarization. Two analytical models are utilized for preliminary evaluation of MG parameters. One of them determines the top limit of T(f) variations, where T is transmittance and f is frequency. The other model determines the bottom limit. The given models were implemented in assumption of small reflections in microwave network. MG size defines one of the restrictions on their application.